Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22094774
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Deruxtecan: Changing the Destiny of HER2 Expressing Solid Tumors

Abstract: HER2 targeted therapies have significantly improved prognosis of HER2-positive breast and gastric cancer. HER2 overexpression and mutation is the pathogenic driver in non-small cell lung cancer (NSCLC) and colorectal cancer, however, to date, there are no approved HER2-targeted therapies with these indications. Trastuzumab deruxtecan (T-DXd) is a novel HER2-directed antibody drug conjugate showing significant anti-tumor activity in heavily pre-treated HER2-positive breast and gastric cancer patients. Prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 48 publications
(89 reference statements)
0
47
0
1
Order By: Relevance
“…Companion diagnostic criteria of HER2 expression in NSCLC is suggested as follows: (i) 0, HER2 expression negative; (ii) 1+, currently considered to be negative. With the increased application of ADC therapy and update of research evidence, 87 however, it needs to be confirmed whether 1 + should be considered to be HER2 expression negative or HER2 -low expression; (iii) 2+, 3+: HER2 expression positive.…”
Section: Recommendations For Her2 Alterations Test...mentioning
confidence: 99%
“…Companion diagnostic criteria of HER2 expression in NSCLC is suggested as follows: (i) 0, HER2 expression negative; (ii) 1+, currently considered to be negative. With the increased application of ADC therapy and update of research evidence, 87 however, it needs to be confirmed whether 1 + should be considered to be HER2 expression negative or HER2 -low expression; (iii) 2+, 3+: HER2 expression positive.…”
Section: Recommendations For Her2 Alterations Test...mentioning
confidence: 99%
“…Interestingly, the DrugBank analysis showed that the drug targeting GAA was Trastuzumab-deruxtecan. Trastuzumab-deruxtecan is primarily used for patients with human epidermal growth factor receptor 2 (HER2)-mutant tumours including non-SCLC and in the absence of SCLC (79)(80)(81). Upon binding to HER2, Trastuzumab-deruxtecan disrupts the HER2 signalling, undergoes internalisation and intracellular linker cleavage by lysosomal enzymes and ultimately causes DNA damage and apoptotic cell death (80).…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab-deruxtecan is primarily used for patients with human epidermal growth factor receptor 2 (HER2)-mutant tumours including non-SCLC and in the absence of SCLC (79)(80)(81). Upon binding to HER2, Trastuzumab-deruxtecan disrupts the HER2 signalling, undergoes internalisation and intracellular linker cleavage by lysosomal enzymes and ultimately causes DNA damage and apoptotic cell death (80). In addition, Martinho et al found that the inhibitors of the HER family (mainly HER2) reduced cervical cancer aggressiveness by blocking glucose metabolism (82).…”
Section: Discussionmentioning
confidence: 99%
“…The ERBB2 gene encodes the human epidermal growth factor receptor 2 (HER2) receptor tyrosine kinase (RTK), a member of the epidermal growth factor receptor (EGFR)related family of RTKs, and ligand-independent activation of HER2 can result from HER2 overexpression or ERBB2 amplification (ERBB2amp). [1][2][3][4] HER2-targeted therapy revolutionized cancer care by providing one of the first demonstrations of clinical utility of biomarker-selected approaches and led to the approval of anti-HER2 therapies in breast cancers with HER2 overexpression. [5][6][7] The anti-HER2 therapy trastuzumab is also approved in advanced gastroesophageal adenocarcinoma (advGEA) in combination with first-line chemotherapy on the basis of results from the Trastuzumab for Gastric Cancer trial, 8 and investigational use of anti-HER2 therapies is being explored in other tumor types including colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%